Strengthening Local Culture-Based Character Education - Irsyadiah, Nur; Sulaeman, Maryam; Marlina, Yuli; Siregar, Mulki (STAI Miftahul Ula Nganjuk, 2024)
When diversity causes numerous multi-dimensional challenges for the Indonesian country, it is thought important to reorganize character education. The purpose of this research is to create a descriptive image of how to develop local culture-based character education for pupils. An ethnographic approach is used in the descriptive qualitative research method.. The data sources used are primary data and secondary data. This research is located at the Daarul Qur'an Al Ismailliyah Foundation in Kalianda, South Lampung. Research results: 1) Integrating the values of character education in the curriculum in each subject, consistent habituation from the start of school entry to the end of the activity, routinely carrying out Dhuha prayers in congregation, reading Asmaul Husna and reading the Qur'an, performing arts and martial arts exercises regularly, character education based on local culture focuses on discipline, there is an evaluation of the implementation of school regulations by doing morning assembly regularly. related to local culture-based character education, providing a sustainable understanding of local culture,